Salivary oxidative stress persists in inflammatory bowel disease regardless of biological treatment response - Bigagli, Elisabetta; Innocenti, Tommaso; Dragoni, Gabriele; Pindozzi, Francesco; Galli, Andrea; Lodovici, Maura; Luceri, Cristina (Frontiers in Pharmacology, 2025)
BackgroundUncontrolled oxidative stress contributes to the pathogenesis of inflammatory bowel disease (IBD), yet its association with disease activity and response to biological therapy, has never been studied in saliva. We investigated whether salivary oxidative stress markers could predict therapeutic response to biologics in IBD patients.MethodsSeventy-three IBD patients (46 ulcerative colitis (UC), 27 Crohn’s disease (CD)) eligible for infliximab or vedolizumab and 56 healthy controls (HC) were enrolled. Salivary advanced oxidation protein products (AOPPs), advanced glycated end-products (AGEs), and ferric reducing antioxidant power (FRAS) were measured at baseline and at week 26. Clinical response was assessed at weeks 26 and 52, and endoscopic activity at baseline and week 52.ResultsBaseline AOPPs and AGEs were higher in IBD than HC (p < 0.0001), but only AOPPs distinguished mild from moderate-severe endoscopic activity (AUC 0.72; p < 0.05). Clinical response at week 26 was 77.8% in CD and 69.6% in UC, yet AOPPs remained stable from baseline. Endoscopic remission at week 52 occurred in 40.7% of CD and 23.9% of UC patients. Neither baseline nor 26-week AOPPs or AGEs predicted endoscopic improvement or remission.ConclusionSalivary AOPPs reflect baseline disease severity but do not predict response to biologics. Persistent AOPPs accumulation despite clinical control suggests a decoupling between clinical remission and oxidative homeostasis. Understanding the drivers and clinical relevance of persistent AOPPs is needed before considering potential therapeutic applications, such as antioxidant-based adjunctive strategies or interventions targeting AOPP-mediated damage, to improve remission rates in IBD patients receiving advanced treatments.